2007
DOI: 10.1007/s00167-007-0394-9
|View full text |Cite
|
Sign up to set email alerts
|

Flexion gap preparation opens the extension gap in posterior cruciate ligament-retaining TKA

Abstract: It has been reported that preparation of the flexion gap results in significant widening of the prepared extension gap in posterior stabilized (PS) total knee arthroplasty (TKA). To date, there is a paucity of data regarding cruciate ligament-retaining (CR) TKA. Changes in the extension gap caused by preparation of the flexion gap were measured in 42 varus osteoarthritic knees undergoing CR TKA. The extension gap was first prepared and then measured before and after preparation of the flexion gap. The extensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…Many surgeons strive to produce extension and flexion gaps that are of equal magnitude and/or symmetrical [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Many surgeons strive to produce extension and flexion gaps that are of equal magnitude and/or symmetrical [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Even preparation of the flexion gap can influence the extension gap. Minoda et al 17 found that preparation of the flexion gap resulted in significant widening of the extension gap during cruciate-retaining TKA. Also, Sugama et al 18 showed a significant increase in the width of the extension gap, and hypothesized that the removal of the posterior femoral condyle and osteophytes loosens the posterior capsule and thus affects the extension gap.…”
mentioning
confidence: 99%
“…These procedures were difficult to perform before femoral osteotomies. Minoda et al assessed the three different extension gaps before and after femoral osteotomy of the posterior condyle, and after removal of femoral posterior osteophytes [33]. In the future, we need to further investigate the effect of these procedures at flexion as well as at extension.…”
Section: Discussionmentioning
confidence: 98%
“…In the procedure using the gap technique, the extension gap has been reported to be wider after resection of the posterior femoral condyle and removal of the osteophytes on the posterior aspect of the femur, a procedure performed to reestablish the posterior capsular recess in CR TKA [33] as well as PS TKA [31]. Therefore, if the flexion gap is matched to the previously prepared extension gap, the extension gap will increase, and the flexion gap will become smaller than the extension gap.…”
Section: Discussionmentioning
confidence: 98%